Relationship Between Social Motivation in Children With Autism Spectrum Disorder and Their Parents - Uljarević, Mirko; Frazier, Thomas W.; Jo, Booil; Phillips, Jennifer M.; Billingham, Wesley; Cooper, Matthew N.; Hardan, Antonio Y. (Frontiers in Neuroscience, 2021)
The current study aimed to characterize the relationship between parental and proband social motivation. Data from 2,759 children with ASD (Mage = 9.03 years, SDage = 3.57, 375 females) and their parents from the Simons Simplex Collection (SSC) project was included in this study. Parental and proband social motivation (SM) was assessed using previously identified item sets from the Social Responsiveness Scale (SRS). Children who had parents with low SM scores (less impairments) showed significantly lower impairments in social motivation compared to children who had either one or both parents with elevated SM scores. No parent-of-origin effect was identified. Although no significant interactions were found involving proband sex or intellectual disability (ID) status (presence/absence of intellectual disability) with paternal or maternal SM, the point estimate of the paternal effect on a male child was over three-fold higher than the effect on a female child. This study establishes that low social motivation in children with ASD may be driven, in part, by lower social motivation in one or both parents. Future investigations should utilize larger family pedigrees, including simplex and multiplex families, evaluate other measures of social motivation, and include other related, yet distinct constructs, such as social inhibition and anhedonia. This will help to gain finer-grained insights into the factors and mechanisms accounting for individual differences in sociability among typically developing children as well as those with, or at risk, for developing ASD.